Safety Evaluation of Porcine Bile Acids in Laying Hens: Effects on Laying Performance, Egg Quality, Blood Parameters, Organ Indexes, and Intestinal Development - Yang, Bowen; Huang, Shimeng; Li, Shupeng; Feng, Zhihua; Zhao, Guoxian; Ma, Qiugang (Frontiers in Veterinary Science, 2022)
Bile acids (BA) have long been known to facilitate digestion, transport, and absorption of lipids in the small intestine as well as regulate host lipid metabolic homeostasis. However, BA in excess can lead to long-term damage to tissue. Also, it is unknown whether different levels of porcine BA supplementation could improve performance, host metabolism, intestinal functions in laying hens. Hence, this study was aimed to investigate the potential effects of BA supplementation on production performance, egg quality, blood parameters, organ indexes, and intestinal histopathology of hens in the late phase. A total of 300 58-week-old Hy-line Grey hens were randomly divided into five groups and fed a basal diet (control) or basal diets supplemented with BA at 60, 300, 600, and 3,000 mg/kg for 56 days. Compared with the control group, no significant differences (P > 0.05) were observed in the egg production, egg weight, ADFI, and FCR of hens in the 60, 300, 600, and 3,000 mg/kg groups. Dietary 60 mg/kg BA supplementation resulted in a significant increase (P < 0.05) in egg mass than the control group. Meanwhile, these results showed that no significant differences (P > 0.05) were observed in the egg quality, including eggshell strength, albumen height, and Haugh unit among any treatment groups. Dramatically, 3,000 mg/kg BA decreased (P < 0.05) yolk color compared with the control group. There was on significant difference in the blood parameters WBC, RBC, HGB, HCT, and PLT and organ coefficients (including kidney, testis, liver, and spleen coefficient) among any treatments of laying hens. But ovary coefficient in 3,000 mg/kg BA group decreased (P < 0.05). Interestingly, these harmful effects were begun to appear (P < 0.05) at the highest dosage (3,000 mg/kg) of BA supplementation in the histopathological scores and plasma biomarkers of kidneys and oviducts in laying hens. These results indicated that a porcine BA concentration of 600 mg/kg was non-deleterious to laying hens after a daily administration for 56 days, namely that dietary supplementation of up to 10 times the recommended dose of BA is safely tolerated by laying hens.